(untitled) (Journal of actual problems of jurisprudence, 2020)
The use of electronic means of monitoring the conduct of persons released from prison on parole and suspects for whom preventive measures are applied without detention, including those under house arrest. Electronic search and identification systems. The modernization of the law enforcement system should be carried out by means of simplifying the process of justice, freeing it from unnecessary bureaucratic procedures with the active introduction of new information technologies. The purpose of this article is to investigate the latest computer programs and their application in the activities of the internal affairs agencies. The article also speaks about application of special knowledge and skills of specialists, i.e. about other level of application of scientific and technical knowledge and means in criminal proceedings. Computerization has accelerated the transfer and exchange of forensic information received during the investigation between the subjects of criminal activity. In the investigation of crimes, the investigator often resorted to the assistance of specialists and experts. Specialists exist in various fields of science, technology, art and professional skill. With the knowledge and skills of knowledgeable persons, various crimes are solved. Key words: innovative technology, electronic media system, smart technology, type of weapon, information technology, development, influence.